2014
DOI: 10.1039/c4ob00659c
|View full text |Cite
|
Sign up to set email alerts
|

Control of reaction pathways in the photochemical reaction of a quinone with tetramethylethylene by metal binding

Abstract: The present study reports a novel supramolecular photochemical reaction that focuses on the direct electronic interactions between a host reaction substrate and guest metal salts. The reaction pathways in the photochemical reactions of quinone derivatives bearing a methoxy group and a long oligoether sidearm QEn (n = 0 and 3) with tetramethylethylene (TME) are changed upon noncovalent complexations of the host reactant with alkali and alkaline earth metal ions and a transition metal salt. The photochemical rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…For the crystal structure of the related 4-[(2,3-dimethylbut-3en-2-yl)oxy]-3-methoxyphenol, see: Yamamoto et al (2014). For the crystal structure of 3,4,5-trimethoxyphenol, see: Jia et al (2012).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For the crystal structure of the related 4-[(2,3-dimethylbut-3en-2-yl)oxy]-3-methoxyphenol, see: Yamamoto et al (2014). For the crystal structure of 3,4,5-trimethoxyphenol, see: Jia et al (2012).…”
Section: Related Literaturementioning
confidence: 99%
“…Data collection: APEX2 (Bruker, 2014); cell refinement: SAINT (Bruker, 2014); data reduction: SAINT; program(s) used to solve structure: SHELXS97 (Sheldrick, 2008); program(s) used to refine structure: SHELXL2014 (Sheldrick, 2015) and olex2.refine (Bourhis et al, 2015); molecular graphics: OLEX2 (Dolomanov et al, 2009); software used to prepare material for publication: OLEX2 and publCIF (Westrip, 2010 Nguyen et al, 2015), we report herein the structure of 3,4-dimethoxyphenol. A similar 3,4-dialkoxyphenol complex has been structurally characterized (Yamamoto et al, 2014) and…”
Section: Related Literaturementioning
confidence: 99%
“…16 To the best of our knowledge, a stable product has not been known for Paternò-Büchi reaction with unsubstituted PBQ and stilbene; [16][17][18][19][20][21] however, there is a possibility to form an intermediate exciplex of PBQ and stilbene. [22][23][24][25][26] Additionally, the experimental study showed that the [Z]/[E] ratio in the steady-state depended on the concentration of PBQ sensitizer, although such concentration dependence was not found in the reaction which proceeds in the Dexter mechanism. 2 Those findings suggest that a specific intermolecular interaction plays an essential role in the isomerization of stilbene with PBQ sensitizer.…”
Section: Introductionmentioning
confidence: 99%
“…7 We previously reported supramolecular [4 + 2] cycloaddition and [2 + 2] photocycloaddition reactions of a pbenzoquinone derivative bearing an oligoether side-chain that can bind a metal ion through electrostatic interaction. 8,9 The bound metal ion reduces or increases the p-electron density of the quinone, changing its reactivity in both thermal and photochemical reactions. However, to the best of our knowledge, physical operation of the chemical reactions of quinone with the light is an unprecedented subject.…”
mentioning
confidence: 99%